The praxis of leadership styles on employee productivity: a case of the Greater Sekhukhune District Municipality - Majebele, W. (International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa, 2018)
The aim of this study was to investigate the relationship between leadership styles and employee productivity in the Greater Sekhukhune District Municipality, Limpopo Province (South Africa). The study adopted mixed methods in which data was collected through interviews, questionnaires, and document analysis. The study revealed that various leadership styles must be used in an organisation rather than being stagnant in order to address employee productivity or lack thereof. This is important because a leadership style employed by the leader can impact the employees either positively or negatively in regard to performing according to organisational objectives. The findings also revealed that it is important for leaders to involve employees in the decision-making as it assist in bringing about commitment as well as motivating and inspiring employees
Journal article published in The 3rd Annual International Conference on Public Administration and Development Alternatives, 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Employee productivity; Leadership; Leadership styles; Situational Leadership; Leadership; Productivity